Автоматична генерація реалістичних ялин за допомогою математичних моделей у середовищі Blender - Зінченко, А. Я. (ХНУРЕ, 2025)
This work focuses on the automatic generation of realistic 3D spruce trees in Blender. The trees are created using Bézier curves: the trunk is modeled as a segmented curve that gradually narrows upward, while branches are evenly distributed along it, varying in length, thickness, and inclination based on height. To achieve a natural structure, branch placement follows a spiral pattern with controlled randomness. Textured foliage planes with random rotation and tilt enhance realism. Optimization is achieved by grouping elements, reducing system load.
Keywords: 3D spruce trees in Blender; середовище Blender